A novel heterozygous variant in ERLIN2 causes autosomal dominant pure hereditary spastic paraplegia. (15th April 2018) - Rydning, S. L.; Dudesek, A.; Rimmele, F.; Funke, C.; Krüger, S.; Biskup, S.; Vigeland, M. D.; Hjorthaug, H. S.; Sejersted, Y.; Tallaksen, C.; Selmer, K. K.; Kamm, C.
Abstract : Background and purpose: Hereditary spastic paraplegias (HSPs) are clinically and genetically heterogeneous monogenic disorders. To date, nearly 70 genes are known to be causative. The aim of this project was to identify the genetic cause of autosomal dominantly inherited pure HSP in two large, unrelated non‐consanguineous families. Methods: The two families were characterized clinically and selected members underwent whole exome sequencing. Potentially disease‐causing variants were confirmed by Sanger sequencing and their functional consequences on protein function were predicted by bioinformatic prediction tools. Results: The patients presented with pure spastic paraplegia with age of onset between 9 and 46 years. In both families, a novel heterozygous missense variant in ERLIN2, c.386G>C; p.Ser129Thr, was the only potentially pathogenic variant identified that segregated with the disease. Conclusions: Biallelic variants in ERLIN2 are known to cause recessive HSP type SPG18. Here, the first two families with an autosomal dominant, pure form of HSP caused by a novel ERLIN2 heterozygous missense variant are described. These findings expand the mutational and inheritance spectrum of SPG18. ERLIN2 variants should also be considered in the diagnostic evaluation of patients with autosomal dominant HSP.